Consuming pleasures : active audiences and serial fictions from Dickens to soap opera - Hayward, Jennifer Poole (Lexington : University Press of Kentucky, 1997)
""To be continued... "" Whether these words fall at a season-ending episode of Star Trek or a TV commercial flirtation between coffee-loving neighbors, true fans find them impossible to resist. Ever since the 1830's, when Charles Dickens's Pickwick Papers enticed a mass market for fiction, the serial has been a popular means of snaring avid audiences. Jennifer Hayward establishes serial fiction as a distinct genre -- one defined by the activities of its audience rather than by the formal qualities of the text. Ranging from installment novels, mysteries, and detective fiction of the 1800's.
3 The Future of the Serial Form Audiences and Soap Opera Production; Knowledge and Power: Soap Narrative Strategies; Audiences and Power; Case Study: Redeeming the Rapist; Humor, Irony, and Self-Reflexivity; Tune In Tomorrow; Notes; Bibliography; Index
Includes bibliographical references (pages 207-215) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Television series -- History and criticism; Serialized fiction -- History and criticism; Authors and readers -- History; Séries télévisées -- Histoire et critique; Roman-feuilleton -- Histoire et critique; Écrivains et lecteurs -- Histoire; PERFORMING ARTS -- Television -- Reference; Authors and readers; Serialized fiction; Television series; Fernsehserie; Geschichte; Fortsetzungsroman; Seriewerken; Televisieseries; Engels; Strips; Englisch; Electronic book; Criticism, interpretation, etc; History